UJI POLA JAJAR LEGOWO PADA BEBERAPA VARIETAS PADI SAWAH (Oriza sativa L.) BUDIDAYA SRI - Purwanto, Edi; Rauf, Abdul; Made, Usman (AGROTEKBIS, 2017)
This research is aimed to know the right legowo row pattern on each rice varieties of SRI cultivation. This research was arranged with factorial design using Randomized Block Design (RBD) as environmental design. The first factor is legowo row pattern consisting of legowo row pattern 2:1, legowo row pattern 3:1, and legowo row pattern 4:1 and second factor varieties consisting of varieties Mekongga, Ciherang and IPB 4S. Each treatment combination is repeated three times. The result of this research shows that the Mekongga varieties produced moreÂ number of tillers and the number of panicles, while the varieties of IPB 4S showed more longer panicles and the number of grains per panicl, and Ciherang varieties not only produced more number of tillers and number of panicles but also produced 1000 seeds more weighs, resulting in higher productivity. 2:1 legowo row pattern is better shown on Ciherang and IPB 4S varieties, while the 3:1 legowo row pattern is better shown on the Mekongga variety.Â Keywords: Variety, legowo row pattern, Rice, and SRI Cultivation.